2021
DOI: 10.3390/foods10092111
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin Reduces Lignification and Retains Quality of Green Asparagus (Asparagus officinalis L.)

Abstract: Asparagus (Asparagus officinalis L.) is highly perishable because of its high respiration rate, which continues after harvesting and leads to weight loss, increased hardness, color change, and limited shelf life. Melatonin is an indoleamine that plays an important role in abiotic stress. This study was designed to investigate the effects of melatonin on the quality attributes of green asparagus during cold storage. Green asparagus was soaked in a melatonin solution (50, 100, and 200 μM) for 30 min and then sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Lignin levels in seedlings can be quantified by A 280 in UV spectrophotometry [ 30 ]. These results indicated that high dose LGC up-regulated phenylalanine metabolism and the phenylpropanoid pathway and increased lignin expression levels, which would solidify the cell wall and inhibit root growth [ 31 ]. On the contrary, a low concentration of LGC down-regulated the metabolism of phenylalanine and the synthesis pathway of precursors of lignans, phenylpropanoid, which would inhibit the expression level of lignans and promote plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Lignin levels in seedlings can be quantified by A 280 in UV spectrophotometry [ 30 ]. These results indicated that high dose LGC up-regulated phenylalanine metabolism and the phenylpropanoid pathway and increased lignin expression levels, which would solidify the cell wall and inhibit root growth [ 31 ]. On the contrary, a low concentration of LGC down-regulated the metabolism of phenylalanine and the synthesis pathway of precursors of lignans, phenylpropanoid, which would inhibit the expression level of lignans and promote plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different studies, washing times vary from 30 s to 24 h depending on the tested compounds. Boonsiriwit et al . noted that melatonin treatment (100 μM) for 30 min effectively maintained green asparagus postharvest quality (i.e., color, texture) during cold storage (4 °C) for 25 days by delaying chlorophyll degradation and reducing lignin content.…”
Section: Postharvest Treatments For Minimizing Physiological Disorder...mentioning
confidence: 99%
“…Among the different studies, washing times vary from 30 s to 24 h depending on the tested compounds. Boonsiriwit et al 83 noted that melatonin treatment (100 μM) for 30 min effectively maintained green asparagus postharvest quality (i.e., color, texture) during cold storage (4 °C) for 25 days by delaying chlorophyll degradation and reducing lignin content. Melatonin delayed lignin increase by decreasing PAL and POD activities, while it delayed asparagus senescence and chlorophyll degradation by enhancing the activities of the antioxidant enzymes CAT and SOD, that react and deactivate ROS.…”
Section: Artificial Lightmentioning
confidence: 99%
“…Melatonin treatment could increase pomegranate fruit quality, especially the aril color and antioxidant components at harvest and storage periods ( Lorente-Mento et al, 2021 ). The compound also improved the postharvest quality of green asparagus ( Boonsiriwit et al, 2021 ) and mushroom ( Lin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%